Featured Cover. (20th August 2022) - Jia, Zhiyuan; Luo, Yangjun; Takezawa, Akihiro; Zhang, Xiaopeng
Abstract : The cover image is based on the Research Article Topology optimization for realizing tailored self‐collimation in phononic crystals by Xiaopeng Zhang et al., https://doi.org/10.1002/nme.7004 .